Luxury : a rich history - McNeil, Peter, 1966-; Riello, Giorgio (Oxford University Press, 2016)
The first ever global history of luxury, from Roman villas to Russian oligarchs: a sparkling story of novelty, excess, extravagance, and indulgence through the centuries.